Improving As(iii) adsorption on graphene based surfaces: impact of chemical doping1. Issue 18 (14th May 2015) - Cortés-Arriagada, Diego; Toro-Labbé, Alejandro
<x xml:space="preserve">Abstract</x> On the basis of quantum chemistry calculations, the adsorption of As(iii) onto graphene based adsorbents has been studied.